Varnost v lokalnih skupnostih – med ruralnimi in urbanimi perspektivami - Meško, Gorazd (2021)
Safety and Security in Local Communities - Between Rural and Urban Perspectives. The monograph presents eight thematically rounded chapters, the main topic of which is safety and security in local communities and the dividing line between safety in rural and urban environments. The monograph is the result of scientific research work of members of the program group Security and Safety in Local Communities - A Comparison of Rural and Urban Settings, which is carried out at the Institute of Criminal Justice and Security, Faculty of Criminal Justice and Security, University of Maribor. The authors come from various fields on the criminal justice and security spectrum, so they approach the extensive topic in their chapters from different angles. Some chapters are more theoretical in nature and examine various aspects of security, while some chapters are also the product of empirical research on security issues in rural and urban local communities.
Keywords: Slovenia; Safety and security; local communities; rural environment; urban environment